Investigation of outbreaks of Pneumocystis jirovecii pneumonia in two Scottish renal units. Issue 2 (June 2017) - Inkster, T.; Dodd, S.; Gunson, R.; Imrie, L.; Spalding, E.; Packer, S.; Deighan, C.; Daly, C.; Coia, J.; Imtiaz, T.; McGuffie, C.; Wilson, R.; et al.
Summary: Pneumocystis jirovecii is recognized as an opportunistic pathogen. In recent years, human-to-human transmission of P. jirovecii has been demonstrated. However, outbreaks of P. jirovecii infections are not well defined because the epidemiological setting that facilitates transmission is not fully understood. This article describes two outbreaks of P. jirovecii pneumonia (PCP) in renal transplant patients in the West of Scotland. In total, 25 patients in two geographically contiguous locations were affected. Allele B was identified as the dominant type, along with allele A3. It was not possible to determine the exact reason for clustering of cases, although the outpatient clinic setting featured in one of the outbreaks. The outbreaks ceased with the use of trimethoprim-sulphamethoxazole prophylaxis; the target populations that received prophylaxis were different in the two outbreaks. Infection control teams should be alert to the possibility of outbreaks of PCP.